Efektifitas Metode Pembelajaran Timeline Terhadap Hasil Belajar Pendidikan Agama Islam - Suhirman Suhirman (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: The Effectiveness of the Timeline Learning Method on Learning Outcomes of Islamic Religious Education.The purpose of this study was to test the effectiveness of the Timeline Learning Method on the learning outcomes of Islamic Religious Education in 11th grade students at Madrasah Aliyah Negeri 2 Bengkulu City. This type of research is quantitative with a quasi-experimental approach. Data collection techniques using observation, tests, and documentation. The results of this study indicate: a). there is an increase in student learning outcomes after using the Timeline learning method in learning Islamic Religious Education 11th grade at MAN 2 Bengkulu City, b) a comparison of the Timeline and Concept Map learning methods: the Timeline learning method increases by 1%, the learning outcomes students will experience an increase of 0.580, and the Concept Map learning method increases 1%, so student learning outcomes increase by 0.336..Abstrak: Metode Pembelajaran Timeline, Concept Map, dan Hasil Belajar.Tujuan penelitian ini untuk menguji Efektifitas Metode Pembelajaran Timeline terhadap hasil belajar Pendidikan Agama Islam pada peserta didik kelas XI Madrasah Aliyah Negeri 2 Kota Bengkulu. Jenis penelitian ini merupakan kuantitatif dengan pendekatan kuasi eksperimen. Teknik Pengumpulan data menggunakan observasi, tes, dan dokumentasi. Hasil penelitian ini menunjukkan: a).terdapat peningkatan hasil belajar siswa setelah menggunakan metode pembelajaran Timeline dalam pembelajaran Pendidikan Agama Islam Kelas XI di MAN 2 Kota Bengkulu,  b) perbandingan metode pembelajaran Timeline dan Concept Map: metode pembelajaran Timeline meningkat 1% maka hasil belajar siswa akan mengalami peningkatan 0,580, dan metode pembelajaran  Concept Map meningkat 1% maka hasil belajar siswa meningkat sebesar 0,336.